Advances in adhesion interfaces of peripheral nerve repair materials: mechanism, classification, evaluation method, and functionalization - Meng, Qi; Zhang, Meng; Zhang, Yichong; Jiang, Haoran; Qu, Yang; Li, Ci; Hu, Chenyujun; Lin, Zhihao; Xing, Bohan; Zhu, Fengxue; Zhang, Peixun (Frontiers in Cell and Developmental Biology, 2025)
Peripheral nerve injury is a prevalent clinical disease, but achieving functional recovery remains a significant research challenge. In recent years, the therapeutic efficacy of nerve repair materials has garnered widespread attention from researchers. Notably, the adhesion interface between the repair material and the nerve tissue stands as a critical factor affecting the outcome of nerve regeneration. In this review, we firstly outline the importance of adhesion interface in nerve repair; subsequently, we systematically summarize the typical adhesion mechanisms; in addition, we discuss the design of adhesion interfaces for natural and synthetic materials, as well as the dry and wet adhesion strategies. To address the in vivo wet environment, emphasis is placed on the adhesion design of wet-adhesive materials and related research progress. Furthermore, methods to evaluate adhesion property and strategies for materials functionalization are also provided. Through summarizing the current research findings, this paper aims to provide theoretical basis and technical reference for the optimal de-sign of interfaces of nerve repair materials, thereby facilitating the clinical translational application of peripheral nerve injury repair materials.